Edible Coatings Fortified With Carvacrol Reduce Campylobacter jejuni on Chicken Wingettes and Modulate Expression of Select Virulence Genes - Shrestha, Sandip; Wagle, Basanta R.; Upadhyay, Abhinav; Arsi, Komala; Upadhyaya, Indu; Donoghue, Dan J.; Donoghue, Annie M. (Frontiers in Microbiology, 2019)
Campylobacter jejuni, a leading cause of foodborne disease in humans, associate primarily with consumption of contaminated poultry and poultry products. Intervention strategies aimed at reducing C. jejuni contamination on poultry products could significantly reduce C. jejuni infection in humans. This study evaluated the efficacy of gum arabic (GA) and chitosan (CH) fortified with carvacrol (CR) as an antimicrobial coating treatment for reducing C. jejuni on chicken wingettes. Aforementioned compounds are generally recognized as safe status compounds obtained from gum arabic tree, crustaceans and oregano oil respectively. A total of four separate trials were conducted in which wingettes were randomly assigned to baseline, saline control (wingettes washed with saline), GA (10%), CH (2%), CR (0.25, 0.5, or 1%) or their combinations. Each wingette was inoculated with a cocktail of four wild-type strains of C. jejuni (∼7.5 log10 cfu/sample). Following 1 min of coating in aforementioned treatments, wingettes were air dried (1 h) and sampled at 0, 1, 3, 5, and 7 days of refrigerated storage for C. jejuni and total aerobic counts (n = 5 wingettes/treatment/day). In addition, the effect of treatments on wingette color was measured using a Minolta colorimeter. Furthermore, the effect of treatments on the expression of C. jejuni survival/virulence genes was evaluated using real-time quantitative PCR. Results showed that all three doses of CR, CH or GA-based coating fortified with CR reduced C. jejuni from day 0 through 7 by up to 3.0 log10 cfu/sample (P < 0.05). The antimicrobial efficacy of GA was improved by CR and the coatings reduced C. jejuni by ∼1 to 2 log10 cfu/sample at day 7. Moreover, CH + CR coatings reduced total aerobic counts when compared with non-coated samples for a majority of the storage times. No significant difference in the color of chicken wingettes was observed between treatments. Exposure of pathogen to sublethal concentrations of CR, CH or combination significantly modulated select genes encoding for energy taxis (cetB), motility (motA), binding (cadF), and attachment (jlpA). The results suggest that GA or CH-based coating with CR could potentially be used as a natural antimicrobial to control C. jejuni in postharvest poultry products.